DOMUL, PORTAL INTERCULTURAL AL PLURALITĂȚII RELIGIOASE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
The Dome, an Intercultural Portal for Religious Plurality.In a globalized world interactions between religious communities generate both dialogue and tolerance, as well as tensions. Individualism can weaken relationships with religious traditions, while diversity can amplify extremism when religious identities are perceived as being threatened. The paper highlights ecumenical initiatives that promote dialogue and respect between different confessions, emphasizing the essential role of education in combating extremism and supporting peaceful coexistence. A central focus of the study is the proposal for an innovative educational workshop based on the use of a geodesic dome, a symbol of unity in diversity. This is not only an architectural structure but also a pedagogical symbol of cultural and religious interconnectedness, reflecting the idea that, although beliefs may vary, there are common values that can facilitate intercultural dialogue. In the workshop, the dome serves as a bridge between spiritual and cultural realms, creating an immersive space where participants can explore religious diversity. Theoretical and practical activities help young people better understand common beliefs and values, promoting respect, tolerance, and social cohesion. Thus, the dome becomes a metaphor for religious pluralism, emphasizing the complexity and interdependence of the modern world. The structure also functions as a portal for exploring cultural and temporal dimensions, offering a multisensory and interdisciplinary educational experience that contributes to the development of critical and collaborative thinking. Through this approach, the geodesic dome becomes a symbol of unity and intercultural cooperation, promotingreligious pluralism and the formation of moral and well-informed citizens, capable of navigating the complexities of the globalized world.